2018
DOI: 10.1155/2018/3567306
|View full text |Cite
|
Sign up to set email alerts
|

Flavoprotein Fluorescence Correlation with Visual Acuity Response in Patients Receiving Anti‐VEGF Injection for Diabetic Macular Edema

Abstract: Anti-VEGF treatment of diabetic macular edema (DME) complicating diabetic retinopathy (DR) has greatly improved structural and visual outcomes for patients with diabetes mellitus. However, up to 50% of patients are either nonresponsive or refractory to anti-VEGF treatment (no improvement in BCVA or central macular thickness (CMT)). It is believed that factors such as mitochondrial structural and functional damage, due to oxidative stress, are partially responsible for this lack of improvement. Flavoprotein flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…10,18 Previous studies have demonstrated the utility of FPF in detecting retinal metabolic stress in diabetic retinopathy, 12 with correlations found between FPF and visual acuity responses in patients undergoing treatment for diabetic macula edema independent of OCT findings. 19 The patients with age-related macular degeneration, central serous chorioretinopathy retinal dystrophies, ocular hypertension, and primary open angle glaucoma have also been found to have the higher retinal FPF scores indicative of mitochondrial dysfunction in various observational studies. 11,13,20,21 More recently, FPF measurements have been obtained from the optic disc rim and found to be increased in POAG patients compared with controls, 14 although advances in software computational algorithms for FPF mean that our scores were not directly comparable with prior studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,18 Previous studies have demonstrated the utility of FPF in detecting retinal metabolic stress in diabetic retinopathy, 12 with correlations found between FPF and visual acuity responses in patients undergoing treatment for diabetic macula edema independent of OCT findings. 19 The patients with age-related macular degeneration, central serous chorioretinopathy retinal dystrophies, ocular hypertension, and primary open angle glaucoma have also been found to have the higher retinal FPF scores indicative of mitochondrial dysfunction in various observational studies. 11,13,20,21 More recently, FPF measurements have been obtained from the optic disc rim and found to be increased in POAG patients compared with controls, 14 although advances in software computational algorithms for FPF mean that our scores were not directly comparable with prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…With mitochondrial dysfunction now understood to play a critical role in glaucomatous optic neuropathy, FPF has emerged as a potential novel biomarker among noninvasive options being developed 10,18. Previous studies have demonstrated the utility of FPF in detecting retinal metabolic stress in diabetic retinopathy,12 with correlations found between FPF and visual acuity responses in patients undergoing treatment for diabetic macula edema independent of OCT findings 19. The patients with age-related macular degeneration, central serous chorioretinopathy retinal dystrophies, ocular hypertension, and primary open angle glaucoma have also been found to have the higher retinal FPF scores indicative of mitochondrial dysfunction in various observational studies 11,13,20,21.…”
Section: Discussionmentioning
confidence: 99%
“…Significant FPF elevation is detected in nAMD patients [242]. Discovery of FPF led to a quantifying technique for FPF emission from a patient's retina, developing imaging tests based on metabolic indicator for predicting disease progression in the retina [243][244][245][246].…”
Section: Metabolic Activity In Namd and Neurodegenerationmentioning
confidence: 99%
“…[242][243][244][245] Newer fundus imaging techniques, such as flavoprotein fluorescence (FPF) may allow the detection of metabolic improvements that precede structural improvements in DME patients receiving anti-VEGF injections. 246 Functional testing of macular sensitivity utilizing microperimetry and electroretinography is also being increasingly used in both DR and DME to assess both disease severity and response to therapy. [247][248][249][250][251][252][253][254][255][256][257][258][259][260][261][262] These provide new indices to explore, seeking prognostic value for response to therapy.…”
Section: Future Trends Diagnosticsmentioning
confidence: 99%